Structural and conductivity studies of Li4TisOl2 - Alias, N.A.; Majid, S.R.; Arof, Abdul Kariem (2009)
Li4 isO'2 has been successfully synthesized via the sol-gel method. The powders were calcined at 700 °c, 800 "C, 900 -c and 1000 "C for one hour followed by pellet formation at 500 bars and sintering at 1000 "C for four hours. Electrochemical impedance spectroscopy (EIS) and X-Ray Diffraction (XRD) were employed to characterize the prepared Li4TisO'2. XRD pattern shows that Li4TisO'2 are crystalline and imp rities of the prepared sample pellet can be eliminated by double heat treatment. The conductivity obtained is of the order 10-8 S ern" at room temperature.